Expansion of Secondary Education Programs to Increase Awareness of the Health Risks of Vaping in BC - Tao, Jody (SFU Health Sciences Undergraduate Journal, 2023)
The rate of e-cigarette use among youth has accelerated dramatically in BC, which is particularly concerning given the devastating health consequences of e-cigarettes. Lack of awareness of the health risks of vaping and misconceptions about vaping products contribute to the rise of e-cigarette use among youth. Hence, it is critical that efforts to increase awareness of the health risks of vaping are established. Two interventions aimed at reducing vaping among BC youths are secondary school e-cigarette education programs through (1) the expansion of the physical and health education curriculum and (2) the addition of online learning modules. Implementation of e-cigarette education programs through online learning modules is recommended as they can be established faster and are more cost-effective.